2022
DOI: 10.1093/aobpla/plac029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sublethal single, simultaneous and sequential abiotic stresses on phenotypic traits of Arabidopsis thaliana

Abstract: Plant responses to abiotic stresses are complex and dynamic, and involve changes in different traits, either as the direct consequence of the stress, or as an active acclimatory response. Abiotic stresses frequently occur simultaneously or in succession, rather than in isolation. Despite this, most studies have focused on a single stress and single or few plant traits. To address this gap, our study comprehensively and categorically quantified the individual and combined effects of three major abiotic stresses… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…On the other hand, the s tress response in plants is always accompanied by reprogramming of the metabolism from the photo‐assimilatory to the survival pathway (Chojak‐Kozniewska et al, 2017). Although previous studies have shown detrimental effects of combined stress combinations in crops such as rice (Kadam et al, 2015; Morlaes et al, 2022; Yadav et al, 2022), yet the response of rice to sequential post‐submergence drought stress is unique. For example, submergence regulator SUB1A cross‐talk across submergence and drought stress in rice where SUB1A has been shown to augment ABA responsiveness and ROS scavenging enzymes, hence working efficiently across submergence and drought stress at the vegetative stage (Fukao et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the s tress response in plants is always accompanied by reprogramming of the metabolism from the photo‐assimilatory to the survival pathway (Chojak‐Kozniewska et al, 2017). Although previous studies have shown detrimental effects of combined stress combinations in crops such as rice (Kadam et al, 2015; Morlaes et al, 2022; Yadav et al, 2022), yet the response of rice to sequential post‐submergence drought stress is unique. For example, submergence regulator SUB1A cross‐talk across submergence and drought stress in rice where SUB1A has been shown to augment ABA responsiveness and ROS scavenging enzymes, hence working efficiently across submergence and drought stress at the vegetative stage (Fukao et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a substantial impact of submergence and post‐submergence drought stress has been observed on gas exchange traits and photosynthesis machinery in this genotype (Figure 4). Morales et al (2022) have shown that drastic reduction in light intensity, stomatal conductance, and photosynthesis resulted in severe energy and carbon imbalance in Arabidopsis under submergence stress and post‐submergence drought stress. Yeung et al (2018) further demonstrated how the post‐submergence phase is associated with new stressors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another consideration is that two stresses, which individually cause opposite adaptations, occur simultaneously (Figure 1b). Collision of such opposing pathways may lead to intermediate phenotypes that might or might not be beneficial for tolerance (Morales et al., 2022). Contrastingly, it is possible that one stressor is dominant and overwrites the response of a combined secondary stressor (Morales et al., 2022; Sewelam et al., 2020).…”
Section: Stress Combination In Theorymentioning
confidence: 99%
“…Collision of such opposing pathways may lead to intermediate phenotypes that might or might not be beneficial for tolerance (Morales et al., 2022). Contrastingly, it is possible that one stressor is dominant and overwrites the response of a combined secondary stressor (Morales et al., 2022; Sewelam et al., 2020). However, the number and complexity degree of possible combinations, especially when more than two stressors occur, makes it difficult to predict plant reactions to multifactorial stress combinations.…”
Section: Stress Combination In Theorymentioning
confidence: 99%